2014
DOI: 10.1155/2014/614378
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Coning Correction Structure for Attitude Algorithms

Abstract: A new coning correction structure is presented for attitude update coning correction. Different from the previous rate-based and increment-based coning correction structures, the new structure contains cross-product of angular rates, cross-product of angular increments, and cross-product of angular rate and increment (an angular increment may be approximated from angular rate samples). Two types of optimization methods including time Taylor-series method and frequency Taylor-series method were utilized to desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In the SINS attitude updating, the equivalent rotation vector is generally calculated by using the simple approximation form 1,4,79,12,15,17 where φl is the equivalent rotation vector, t is the time, ω is the gyro sensed angular rate vector at the t time, αl is the integral of ω in time domain [tl-1,tl], and δφl is the analytical form of the coning correction.…”
Section: Coning Correction Structure Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SINS attitude updating, the equivalent rotation vector is generally calculated by using the simple approximation form 1,4,79,12,15,17 where φl is the equivalent rotation vector, t is the time, ω is the gyro sensed angular rate vector at the t time, αl is the integral of ω in time domain [tl-1,tl], and δφl is the analytical form of the coning correction.…”
Section: Coning Correction Structure Designmentioning
confidence: 99%
“…For modern strapdown inertial navigation system (SINS) algorithm, the core technology is the attitude updating algorithm among which the two-stage 1,2 attitude updating algorithm has been widely used. In high precision SINS, the equivalent rotation vector method 2 is necessary, and it requires the attitude noncommutativity error compensation 316 which is commonly referred to as the coning correction of which essence is to numerically approximate the noncommutativity error from gyro data as far as possible. Miller 3 first presented a method of designing a numerical algorithm for the attitude noncommutativity error compensation in the pure coning environment.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the performance evaluation of algorithms including the uncompressed and compressed algorithms can be expressed as the drifting error under coning environment. There are several different forms of multisubsample algorithms, but all of them can be summarized as [9,10] =̃− .…”
Section: The Conventional Structure Of Attitude Algorithmmentioning
confidence: 99%
“…Multisubsample optimized algorithms based on bandwidth of gyroscopes are proposed to restrain drifting of coning error, which are also regarded as uncompressed algorithms. It is found that the more the subsamples are chosen, the smaller the drifting rate of coning error is [6][7][8][9]. To further improve the accuracy of rotation vectors, compressed and half-compressed algorithms have been presented as well [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al divided minor coning correction into a number of subminor intervals and delivered a generalized coning compensation algorithm that is independent of the number of incremental angles [10]. Tang and Chen proposed a coning correction structure containing cross-product of angular rates, cross-product of angular 2 International Journal of Aerospace Engineering increments, and cross-product of angular rate and increment, and it can analyze effect on attitude by basing on time Taylor series and frequency Taylor series [11]. Meanwhile, the gyro frequency response is a primary cause for pseudo-coning error that is another form of coning error, and the traditional coning correction algorithms cannot work to highorder accuracy.…”
Section: Introductionmentioning
confidence: 99%